An investigation into the knowledge, needs, and perspectives of South African professionals working with children with Specific Learning Disorder (Developmental Dyslexia) - Geertsema, Salome (University of Pretoria, 2022)
Dissertation (MA (Speech-Language Pathology)--University of Pretoria, 2021.